Asset-rich and cash-poor: Which older adults value reverse mortgages? - FONG, Joelle H. (Institutional Knowledge at Singapore Management University, 2023)
Home equity represents a substantial share of retirement wealth for many older persons, particularly in Asia where national housing policies have encouraged home-ownership. This paper explored the potential for reverse mortgages to help 'asset-rich and cash-poor' older Singaporeans unlock their home equity while ageing in place. The empirical analysis was based on a nationally representative survey of home-owners age 50+ in the 2018 Singapore Life Panel (N = 6,258). Our analyses showed that the average older home-owner holds some 60 per cent of total net wealth in housing equity, suggestive of high demand potential for reverse mortgage products. Nevertheless, actual interest in such products was much below potential demand. Only one in four older home-owners indicated interest in commercial reverse mortgages if these were to become available; a larger majority had never heard of the financial product. Interest in reverse mortgages was positively associated with product awareness and self-rated product understanding. This implies that a critical step towards building consumer interest would be to enhance awareness of such products and simplify related contract terms. Having a mortgage, fewer children, financial literacy and preparedness for retirement were also positively associated with interest level. These results have implications for targeted interventions to enhance consumer awareness and spur interest in reverse mortgages, especially in ageing societies where older people have built up substantial equity through the housing market over time.